Boron-doped synthetic diamond electrodes and materials
By controlling the nitrogen concentration and optimizing the boron doping concentration in HPHT diamond electrodes, the problem of impaired electrical properties of HPHT electrodes was solved, enabling efficient and low-cost production of diamond electrodes suitable for various electrochemical applications.
Patent Information
- Application Number
- CN202080036605.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-04-09
- Filing Date
- 2020-04-06
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2040-04-06
AI Technical Summary
The control of nitrogen impurities in existing high-pressure high-temperature (HPHT) diamond electrodes is not strict, which leads to the damage of the electrical properties of boron doping and the inability to achieve metal-like conductivity. In addition, CVD diamond electrode production is energy-intensive and costly, and has a small surface area.
By using nitrogen getter materials such as aluminum or aluminum diboride in the HPHT process to control the nitrogen concentration to no more than 10¹⁹ atoms/cm³, and combining high pressure and high temperature synthesis, diamond electrodes with a boron substitution concentration between 1×10²⁰ and 5×10²¹ atoms/cm³ are prepared. Symbiotic grains are formed on the electrode surface or dispersed on conductive or non-conductive matrix materials to form a porous or compacted structure.
A low-nitrogen-doped, high-boron-doped diamond electrode has been developed, exhibiting metal-like conductivity, a wide potential window, and low capacitance, making it suitable for electrochemical applications, especially for microelectrodes and supercapacitors due to its high surface area.
Smart Images

Figure CN113840802B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of boron-doped synthetic diamond electrodes and materials. Background Art
[0002] The use of conductive diamond as an electrode material is well known. Such diamond electrodes are very versatile and have a wide range of electrochemical applications, including selective detection and measurement of both inorganic (e.g. heavy metals and cyanides) and organic compounds (e.g. biosensor applications), wastewater treatment (e.g. nitrate reduction) and ozone generation. The wide applicability of diamond electrodes is due to its unique properties: mechanical strength, chemical inertness, low background interference (high signal-to-noise ratio) and wide potential window.
[0003] Diamond is a wide bandgap semiconductor with an indirect bandgap of 5.47 eV, and all known diamond dopants are deep. However, when the boron concentration in diamond is greater than 1×10 20 Atom cm -3 When the acceptor energy level overlaps with the valence band, diamond undergoes a Mott transition and exhibits metal-like conductivity because they obey Ohm's law. Doping below this energy level results in a p-type semiconductor electrode. The electron energy level of the nitrogen donor is too deep in the band gap to produce usable conductivity. Typically, boron-doped diamond (BDD) electrodes are made by chemical vapor deposition (CVD) BDD onto a suitable substrate such as a plate or wire. For example, EP0518532 and US5635258 teach the deposition of a boron-doped diamond layer on a substrate by a chemical vapor deposition method (CVD). US4042673 teaches the synthesis of boron-containing diamond by a high pressure, high temperature (HPHT) solvent / catalyst method. In order for the diamond material to exhibit metal-like conductivity, boron must be replaced and doped at a sufficiently high density; in other words, boron must replace carbon atoms in the diamond crystal lattice rather than being present in interstitial positions or as inclusions.
[0004] To illustrate the possible uses of diamond electrodes, US5399247 describes the use of diamond electrodes for wastewater treatment. WO01 / 98766 teaches the use of diamond electrodes in the quantitative analysis of xanthophyll compounds. WO01 / 25508 discloses the production of peroxopyrosulfuric acid using diamond electrodes, and US6106692 teaches methods for quantitatively analyzing a variety of target substances using diamond electrodes.
[0005] The disadvantages of CVD diamond electrodes include that the CVD production process is energy intensive, time consuming, and the resulting electrodes are therefore expensive. The deposition of CVD diamond is planar and produces sheet electrode materials with relatively low surface area. For many electrochemical applications, it is necessary to be able to provide diamond electrodes with a larger surface area than CVD diamond electrodes without significantly sacrificing the desired properties of the electrode, such as robustness and inactivity. WO03 / 066930 describes a porous diamond electrode made of boron-doped diamond polycrystals produced using a high pressure and high temperature (HPHT) method. However, diamond electrodes made in this way generally do not show metal-like conductivity, have a narrow solvent window and therefore exhibit poor electrochemical reversibility to appropriate redox pairs. Summary of the invention
[0006] The object is to provide an improved high pressure high temperature (HPHT) diamond electrode. The inventors have recognised that the presence of certain impurities such as dopants, non-diamond carbon, metals and defects in boron doped diamond material is detrimental to electrical conductivity through the semiconductor mechanism of the material. For boron doped CVD diamond material, the atmosphere during growth of the diamond material is very carefully controlled. However, for HPHT diamond material, contaminants in the atmosphere gas and the raw materials may be incorporated into the diamond. Nitrogen is known to reduce the electrical properties of boron doped diamond because, as a deep level (1.7 eV) n-type dopant, it results in charge compensation with boron and additional charge scattering sites which reduce the number of available charge carriers and the mobility of the charge carriers. Nitrogen is an impurity commonly found in both CVD and HPHT synthetic diamonds. However, for CVD synthetic diamonds, nitrogen can be carefully controlled in the deposition atmosphere. Boron doped CVD diamonds can therefore be produced with nitrogen concentrations several orders of magnitude lower than the boron concentration. Very low levels of nitrogen relative to boron in diamond minimize its compensating effect, so boron-doped CVD diamond is generally an effective conductor. For boron-doped HPHT diamond, nitrogen levels are generally not so tightly controlled, and the amount of nitrogen in the diamond can have an adverse effect on the electrical properties of the boron-doped HPHT diamond, generally resulting in a p-type semiconducting electrode.
[0007] The activation energy level of boron dopants in diamond is 0.37 electron volts (eV) and for metal-like ohmic conductivity (where the measured resistance of an electrode of a defined volume exhibits a linear relationship with current and voltage), boron B>1×10 20 Atom cm -3 , the acceptor level overlaps with the valence band as diamond undergoes a Mott transition to exhibit metallic p-type conductivity. At these doping concentrations there is a significant risk of incorporation of non-diamond carbon and a higher density of defects. Growth conditions have to be carefully controlled to mitigate these effects.
[0008] According to a first aspect, there is provided an electrode comprising a synthetic high pressure high temperature diamond material having a 20 and 5×10 21 Atom / cm 3 The concentration of replacement boron between 19 Atom / cm 3 The electrode has any of the following characteristics:
[0009] In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution 3 / 4-1 / 4 (This is usually when the electrodes are in the form of microelectrodes); and
[0010] In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ A peak-to-peak separation ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution of p (This is typically the case when the electrode is in the form of a microelectrode.) This provides an electrode with a sufficiently high concentration of substitutional boron to act as an electrical conductor, and a sufficiently low concentration of incorporated nitrogen to minimise compensation effects of the nitrogen.
[0011] Alternatively, the sp 2 The carbon content is low enough that no non-diamond carbon peaks appear in the Raman spectrum of the electrode.
[0012] The synthetic high pressure high temperature diamond material optionally has a selected from at least 2×10 20 Boron atom cm -3 , at least 3×10 20 Boron atom cm -3 , at least 5×10 20 Boron atom cm -3 , and at least 7×10 20 Boron atom cm -3 The boron content of any item in.
[0013] In an optional embodiment, the electrode comprises intergrown grains of synthetic high pressure high temperature diamond material.
[0014] In an alternative optional embodiment, the electrode comprises particles of synthetic high pressure high temperature diamond material dispersed in or on an electrically non-conductive matrix material.The non-conductive matrix material is optionally selected from any of a polymer, a perfluorosulfonic acid, an insulating oil and an insulating ink.
[0015] In an alternative optional embodiment, the electrode comprises particles of synthetic high pressure high temperature diamond material dispersed in or on a conductive matrix material.The conductive matrix material is optionally selected from any of a conductive polymer, a non-diamond carbon support, and a conductive ink.
[0016] In an alternative optional embodiment, the electrode comprises a container containing synthetic high pressure high temperature diamond material particles, the container having at least one opening through which the electrolyte can pass in use. Alternatively, the container comprises at least one wall having pores through which the electrolyte can pass in use.
[0017] In an alternative optional embodiment, the electrode comprises a compact of particles of synthetic high pressure high temperature diamond material. Alternatively, the particles of synthetic diamond material have an average particle size selected from any of the ranges of 5 nm to 500 μm, 10 nm to 200 μm, 50 nm to 100 μm, and 100 nm to 10 μm.
[0018] According to a second aspect, there is provided a method of preparing an electrode comprising synthetic high pressure high temperature diamond material, the method comprising:
[0019] Provided is a synthetic high pressure high temperature diamond material having a 20 and 5×10 21 Atom / cm 3 The concentration of replacement boron between 19 Atom / cm 3 nitrogen concentration; and
[0020] Forming synthetic high-pressure and high-temperature diamond material into electrodes.
[0021] The step of forming the synthetic high pressure high temperature diamond material into an electrode optionally comprises providing a reactant comprising high pressure high temperature diamond material and a catalyst material, subjecting the reactant to a temperature greater than 1300°C and a pressure greater than 4.0 GPa to form a body comprising intergrown grains of diamond material, and removing the catalyst material from the body to form the electrode. The catalyst material is optionally selected from any of iron, nickel, cobalt, manganese, and alloys thereof, and the step of removing the catalyst material from the body comprises immersing the body in an acid.
[0022] As an alternative option, the step of forming the synthetic high pressure high temperature diamond material into an electrode comprises dispersing particles of the high pressure high temperature diamond material in or on a non-conductive matrix material. The non-conductive matrix material is optionally selected from any of polymers, perfluorosulfonic acid (Nafion), insulating oil and insulating ink.
[0023] As an alternative option, the step of forming the synthetic high pressure high temperature diamond material into an electrode comprises dispersing particles of the synthetic high pressure high temperature diamond material in or on a conductive matrix material. The conductive matrix material is optionally selected from any of a conductive polymer, a non-diamond carbon support, and a conductive ink.
[0024] As an alternative option, the step of forming the synthetic high pressure high temperature diamond material into an electrode comprises providing a container having at least one opening and placing particles of the synthetic high pressure high temperature diamond material in the container.
[0025] As an alternative option, the step of forming the synthetic high pressure high temperature diamond material into an electrode comprises compacting a plurality of particles of synthetic high pressure high temperature diamond material at a pressure of at least 4.5 GPa and a temperature of at least 1400° C. to form a compact.
[0026] According to a third aspect, there is provided a particle of synthetic high pressure and high temperature diamond material, comprising:
[0027] In 1×10 20 and 5×10 21 Atom / cm 3 The substitutional boron concentration between ; and
[0028] No more than 10 19 Atom / cm 3 nitrogen concentration; and
[0029] Particles of synthetic high pressure, high temperature diamond material having any of the following characteristics:
[0030] In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution 3 / 4-1 / 4 ;and
[0031] In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ A peak-to-peak separation ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution of p .
[0032] Alternatively, the particles of the synthetic high pressure high temperature diamond material have a particle size selected from at least 2×10 20 Boron atom cm -3 , at least 3×10 20 Boron atom cm -3 , at least 5×10 20 Boron atom cm -3, and at least 7×10 20 Boron atom cm -3 The substitutional boron content of any item in.
[0033] The particles of synthetic high pressure high temperature diamond material optionally have a maximum linear diameter selected from any of the ranges of 5 nm to 500 μm, 10 nm to 200 μm, 50 nm to 100 μm, and 100 nm to 10 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to better understand the invention and to show how it functions, embodiments of the invention will now be described, by way of example only, with reference to the accompanying drawings, in which:
[0035] Figure 1 is a flow chart showing exemplary steps for producing HPHT BDD grit and producing compacted BDD disks;
[0036] Figure 2 is a bar graph showing an exemplary size distribution of the resulting HPHT BDD sand particles;
[0037] Figure 3 is a series of FE-SEM images showing the morphology (a and d), surface defects (b and e), and compacted surface structure (c and f) of HPHT BDD particles made from 3.6 wt% AlB2 (ac) and 4.8 wt% AlB2 (df);
[0038] Figure 4 Raman spectra of a) intrinsic diamond and HPHT BDD compacts with a) 3.6 wt% AlB2 and b) 4.8 wt% AlB2 are shown;
[0039] Figure 5 HPHT BDD compacts with a) 3.6 wt% AlB2 and b) 4.8 wt% AlB2 are shown in 0.1 M KNO3 at 0.1 V s -1 Cyclic voltammogram CV recorded at scan rate;
[0040] Figure 6 4.8% AlB2 HPHT BDD compacts in 1 mM Ru(NH3)6 before and after coating with poly(oxyphenylene) and after polishing of the coating are shown. 3+ / 2+ and 0.1M KNO3 at 0.1V s -1 Cyclic voltammogram of
[0041] Figure 7 a is an EBSD image of a SECCM scanned area on a 4.8 wt% AlB2 HPHT BDD compact, and Figure 7b to 7d are the results of the experiments on the 001, 101 and 111 facets in 10 mM Ru(NH3)6Cl3 and 0.01 M KNO3 at 10 V s -1 Recorded cyclic voltammograms;
[0042] Figure 8 a Schematic illustration of the structure of the device, referred to herein as a single particle electrode (SPE), used to probe the electrochemical behavior of a single BDD particle;
[0043] Figure 8 b to 8d show HPHT BDD SPE in 0.1 M KNO3 at 0.1 V s -1 Cyclic voltammograms recorded at scan rates showing b) solvent window, c) typical capacitance curve recorded, and d) HPHT BDD (4.8 wt% AlB2 additive) SPE in 1 mM Ru(NH3)6 3+ / 2+ and 0.1M KNO3 at 0.1, 0.05, 0.02 and 0.005V s -1 The electrode response in the CV recorded at a scan rate of ;
[0044] Fig. 9 Show in Figure 7 FE-SEM image of the top surface of the SiC-polished HPHT BDD SPE shown in a. DETAILED DESCRIPTION
[0045] The inventors have recognised that a significant problem with boron doped diamond grit made using a high pressure high temperature (HPHT) route is that the atmosphere during the HPHT process is typically not controlled. This causes atmospheric nitrogen to be incorporated into the crystal lattice in amounts that can destroy the electrical properties of the substitutionally incorporated boron in the crystal lattice. This means that if the unwanted nitrogen doping in the HPHT diamond is high enough, the HPHT boron doped diamond material may not have the same electrical properties as a CVD boron doped diamond material having the same boron doping level.
[0046] Boron-doped diamond (BDD) grit was prepared using a high pressure and high temperature (HPHT) method. Figure 1 The method is outlined in Figure 1 Number.
[0047] S1. Prepare a reactant comprising a carbon source, a catalyst material, a source of nitrogen getter material, and a boron source. In some cases, it may be desirable to also add diamond seeds to the reactants. An exemplary carbon source is graphite powder. An exemplary catalyst material is a transition metal particle, typically selected from any of iron, nickel, cobalt, manganese, and their alloys or mixtures. During subsequent HPHT operation, the catalyst forms a solvent in which the carbon can be dissolved. Exemplary boron sources include amorphous boron and aluminum diboride. Exemplary nitrogen getter material sources include aluminum powder, titanium powder, and aluminum diboride. Note that aluminum diboride can serve as both a boron source and a nitrogen getter material source.
[0048] S2. Pressurizing the reactants in a HPHT press at a temperature of at least 1100°C and a pressure of at least 3.5 GPa. During pressurization the carbon source dissolves in the catalyst material and precipitates as diamond. Most of the boron from the boron source is incorporated into the diamond crystal lattice by substitution, but some may be incorporated in other forms.
[0049] Note that before pressurization, measures may be taken to reduce the presence of gaseous N2 in the reactants by pre-treatment. This may be done in vacuum and / or using heat treatment and sealing the reactants in a container before pressurizing the reactants in the HPHT press. Other measures may be taken to reduce the presence of nitrogen in the reactants, such as selecting raw materials with low nitrogen concentrations. However, it is important to add a nitrogen getter material to ensure that the nitrogen in the final nitrogen-doped diamond is sufficiently low.
[0050] The nitrogen getter material is any material that reacts with the nitrogen in the reactants during step S2 to form a thermodynamically stable compound in the reactants and therefore will not readily incorporate into the diamond lattice as nitrogen that can electrically compensate for the substitution of boron. For example, when an aluminum source such as elemental aluminum is used, the aluminum will react with the nitrogen in the reactants to form aluminum nitride. Aluminum nitride is thermodynamically stable at the pressurized temperature and pressure. This effectively removes nitrogen from the system and prevents it from being incorporated into the diamond crystal lattice as nitrogen that can electrically compensate for the substitution of boron. Similarly, when an aluminum source such as aluminum diboride is used, the aluminum and boron are separated to allow the aluminum to react with the nitrogen in the reactants in the same manner as described.
[0051] S3. Removing the reactants from the HPHT press and recovering the resulting boron doped diamond (BDD) from the reactants. This can be accomplished, for example, by one or more acid treatments known to those skilled in the art.
[0052] The resulting boron doped diamond material has a much lower level of nitrogen incorporation than boron doped diamond material made without a nitrogen getter in the reactants and therefore has a greater conductivity than boron doped diamond material made without a nitrogen getter in the reactants due to a smaller degree of charge compensation.
[0053] BDD particles can also be used to make compacts or other structures that can be used as electrodes.
[0054] A first exemplary way to form a BDD electrode from particles is to sinter the particles with a solvent / catalyst material at high pressure and temperature to form polycrystalline diamond containing intergrown BDD grains. Acid leaching can be used to remove any remaining catalyst material from the interstices between the grains. The particles can first be ground to a smaller particle size. This will typically leave many particles with cleavage fracture surfaces.
[0055] A typical HPHT regime is to subject the reactants of BDD particles and catalyst material simultaneously to temperatures in the range of 1100°C to 2200°C and pressures of 3.5 GPa to 8 GPa. The catalyst material is typically selected from iron, cobalt, nickel, manganese, and alloys or mixtures thereof. The advantage of electrodes made in this manner is that they are extremely dense.
[0056] A second exemplary way to form a BDD electrode from particles is to disperse the particles in or on a conductive matrix material, such as a conductive polymer / ink or a carbon support. Intimate electrical contact between particles is not necessarily required in this manner.
[0057] A third exemplary way to form a BDD electrode from particles is to disperse the particles in or on a non-conductive matrix, such as perfluorosulfonic acid, mineral oil, insulating polymer or plastic. The particles may or may not be in close contact. For the latter, the particles can be electrochemically detected by bipolar arrangement or by placement on a second conductive support. For example, Nantaphol et al. Anal. Chem., 2017, 89 (7), pp. 4100–4107 describe the use of a paste including boron-doped diamond for microfluidic paper-based analytical devices. Kondo et al. J. Electrochem. Soc., 165 (6) F3072-F3077 (2018) describe boron-doped diamond powder used as a Pt-based cathode catalyst support in a polymer electrolyte fuel cell.
[0058] A fourth exemplary way to form a BDD electrode is to place the particles in a container. The container has an inlet and an outlet, or a porous wall to allow the electrolyte to flow through the container. The container used is placed in the electrolyte and acts as an electrode. In use, the electrolyte can pass through the inlet and outlet (or porous wall) and interact with the BDD diamond particles.
[0059] A fifth exemplary way to form a BDD electrode is to form a compact from particles. Multiple particles are pressed together at a pressure of 4 to 8 GPa and a temperature of at least 1400° C. without any solvent or catalyst material. In this case, at least 95% of the compacted particles are in electrical contact with each other; in other words, when a voltage is applied across one particle, the voltage across all particles in electrical contact with each other increases.
[0060] The present invention will now be described by example.In the first example, 10g of reactant is prepared, which contains 5g of graphite powder (50 wt %), 3.5g of iron powder (35 wt %), 1.5g of nickel powder (15 wt %) and 0.002g of diamond seed crystal.Single steel ball (10mm diameter) is added to reactant and mixed in tank for 30 minutes with turbulent mixer.Then, 1kg of undoped powder batch is prepared, which contains 500g of graphite (50 wt %), 350g of iron (35 wt %), 150g of nickel (15 wt %) and 1.525g of reactant (0.305mg diamond seed crystal / kg).Add 200g of steel ball (10mm diameter) (mass ratio of steel ball to powder 1:5) and use conical mixer to mix 3 hours.Then mix undoped powder and aluminum diboride (AlB2: boron source) to produce a powder mixture containing two different AlB2 concentrations, as shown in Table 1. Again, steel beads (10 mm diameter, 1:5 bead to powder ratio) were added to these powders, which were then mixed using a conical mixer for 1 hour. The boron-containing powder mixture was sieved to remove the beads, and then compacted into cylinders (18 g / piece) and heated to 1050°C under vacuum to remove oxygen and hydrogen impurities. HPHT synthesis was carried out in a stereo anvil HPHT apparatus at approximately 5.5 GPa and 1200°C.
[0061] Table 1 Composition of Boron-containing Powder Mixture
[0062] <![CDATA[AlB2 (wt%)]]> <![CDATA[AlB2(g)]]> Undoped powder mix (g) Total mass (g) 3.6 19.8 530.2 550 4.8 26.4 523.6 550
[0063] BDD particles were recovered from the reactants and purified by a series of acid treatments. The block was first broken into small pieces using a Weber press applying a force of 100 kN. For the subsequent cleaning process, two blocks were recovered simultaneously in the same reaction vessel. First, the broken pieces were heated in HCl (2.0 L) at 250 ° C for 22 hours. When cooled, the solution was decanted through an 80 μm sieve and the acid was poured off. The remaining solid was then rinsed three times with deionized water. Next, BDD was boiled for 22 hours in a 3:1 mixture of H2SO4 and HNO3 at 250 ° C (1.5 L and 0.5 L respectively). Again, the solution was decanted through an 80 μm sieve, the acid was poured off, and the remaining solid was rinsed three times with deionized water. Then, H2SO4 (0.5 L) was added to BDD and heated to 300 ° C. Once boiled, approximately 10 g of KNO3 crystals were added and the solution was left for an additional 30 minutes. Once cooled, the solution was sieved and washed as before. Finally, the BDD particles were added to 100 mL of deionized water in a beaker and placed in an ultrasonic bath for 20 minutes to remove any residual graphite. After this, the waste water was carefully decanted, and the process was repeated until the water remained colorless after ultrasound. Then, this water was also decanted and the BDD particles were dried in a 60°C oven overnight.
[0064] Figure 2 is a bar graph showing an exemplary size distribution of the resulting HPHT BDD sand particles measured by sieving. It can be seen that most of the particles are in the range of 54 to 212 μm. However, one skilled in the art will appreciate that the average particle size can be affected by the time, temperature, and pressure of the HPHT treatment. In addition, it will be appreciated that the particles can be ground or crushed to reduce the average particle size.
[0065] To produce HPHT BDD compacts, approximately 2 g of BDD particles were compacted in a stereo-anvil HPHT apparatus at approximately 6.6 GPa and 1700° C. to produce hot pressed solid BDD disks. Each compact was treated in a mixture of 50 mL HF and 50 mL HNO3 for 24 hours to release the compact from capsule residues. A final degraphitization treatment was applied by annealing at 450° C. in air for 5 hours before polishing one side of each compact to leave a smooth surface for characterization. The produced round compacts had a diameter of approximately 16 mm and a thickness of 2 mm. For electrochemical characterization, titanium (Ti: 10 nm) / gold (Au: 400 nm) contacts were sputtered (Moorfield MiniLab 060 platform sputtering system) onto the rough side of each compact and annealed in air (400° C. for 5 hours) to produce ohmic contacts. Each compact was then placed on a Ti / Au coated glass slide with CircuitWorks conductive silver epoxy (Chemtronics) in contact with both the glass slide and the Ti / Au contacts and dried in a 60°C oven for at least one hour.
[0066] Electrodes were also made from a single BDD particle (only 4.8 wt% AlB2). A metal contact was sputtered onto one end of a single BDD particle and then annealed as described above. Conductive silver epoxy was used to adhere each particle to a segment of PVC insulated copper wire that had been polished to a point with a silicon carbide pad. These were dried in a 60°C oven for at least an hour. These assemblies were then sealed using epoxy (Epoxy Resin RX771C / NC, Aradur Hardener HY1300GB, Robnor Resins) and dried at room temperature for 72 hours. After drying, excess epoxy was removed by careful polishing with a silicon carbide pad that reduced the roughness until the BDD particles were exposed to produce a single particle electrode (SPE).
[0067] The BDD particles and electrodes were characterized in the following manner:
[0068] Raman spectroscopy measurements were performed using a Renishaw inVia Reflex Raman microscope with a 532 nm (2.33 eV) solid-state laser and a laser power of 3.6 mW.
[0069] Field emission scanning electron microscopy (FE-SEM) images of BDD particles and compacts were taken using a Zeiss Gemini 500.
[0070] The nitrogen content of the particles was determined by inert gas fusion infrared and thermal conductivity detection using an ON736 Oxygen / Nitrogen Elemental Analyzer (LECO Corporation).
[0071] Glow discharge mass spectrometry (GDMS) was used to characterize the boron content of the HPHT BDD particles.
[0072] Secondary ion mass spectrometry (SIMS) was used to characterize the boron content of the compacted disks. Note that boron concentration values obtained using SIMS can vary depending on how the SIMS measurement is performed and calibrated. This can be determined by assuming that the ratio of the boron signal is 1 × 10 14 Atom cm -3 Up to 7×10 21 Atom cm -3 SIMS was calibrated using a linear function over the concentration range of . 19 Atom cm -2 The calibration standard was prepared from a single crystal diamond sample with the peak boron concentration at 1 μm depth. The SIMS curve versus sample depth was used to generate a linear calibration factor for the given experimental conditions.
[0073] Note that GDMS and SIMS give information about the total boron content, which includes both free and compensated boron. These are not necessarily an indication of how good the electrical properties of the diamond are. Raman measurements, on the other hand, only show the electrically active boron in the diamond.
[0074] Electrical properties (including solvent window, capacitance and response to redox pairs) are measured by cyclic voltammetry. These are described in detail in WO 2013 / 135783. For boron-doped diamond materials, low boron dopant content (below the metal threshold) can help provide a large solvent window, a flat electrochemical response and a low capacitance. However, such materials will not show metal-like electrochemical properties, resulting in irreversible electrochemical properties for simple and rapid electron transfer outer sphere redox pairs in positive and negative potential windows, and are therefore not ideal for electrochemical sensing applications. Significantly increasing the boron dopant content to metallic conduction levels will cause the solvent window to shrink and the capacitance to increase slightly. In this way, it is believed that there is an optimized range of boron concentration that balances the following requirements: the reversible electrochemical properties of simple and rapid electron transfer outer sphere redox pairs, a relatively large solvent window, a flat electrochemical response and the desired characteristics of low capacitance. In addition, adding too much boron tends to increase the amount of defects in BDD, which negatively affects the electrical conductivity properties.
[0075] In addition to the above, sp 2 Carbon content is undesirable because it also increases the solvent window due to sp 2 The carbon shrinks due to electrocatalysis, increasing the capacitance and making the material appear to be more electrically conductive than it actually is. If the boron dopant content becomes too high, it becomes more difficult to control the formation of non-diamond carbon such as sp 2 The presence of carbon thus provides an additional detrimental effect on the performance of the electrode material in providing a broad, flat baseline for species detection.
[0076] Cyclic voltammetry was performed using a CH Instruments potentiostat (600B, 760E or 800B). A three-electrode droplet cell was set up with a compacted BDD or BDD SPE as a working electrode, a platinum coil counter electrode and a saturated calomel reference electrode (SCE) or Ag / AgCl electrode as a reference. All potentials were listed relative to the reference electrode. Each measurement was recorded for a 1 mm diameter circular area of the exposed surface (exposed using a piece of Kapton tape with a 1 mm diameter circular laser cut hole). Prior to performing the measurement, the surface of each BDD compact was electrochemically cleaned by running a cyclic voltammogram (CV) between -2.0 V and +0.2 V in 0.1 M H2SO4.
[0077] In 0.1M KNO3 at 0.1V s -1 Solvent window and capacitance measurements were run at a scan rate of 0.005 V s -1 To 0.1V s -1CVs recorded over a range of scan rates investigated the fast electron transfer of the outer sphere redox couple Ru(NH3)6 3+ / 2+ After each scan, the surfaces of the BDD compact or BDD SPE, Pt counter electrode, and Ag / AgCl reference electrode were rinsed with deionized water.
[0078] To investigate the material porosity, the polished surface of the HPHT BDD compacts was coated with a thin, uniform, pinhole-free insulating film of polyphenylene ether. This was achieved by electropolymerization of a freshly prepared solution containing 60 mM phenol, 90 mM 2-allylphenol and 160 mM 2-n-butoxyethanol in water / methanol (1:1 by volume). The pH of the monomer solution was adjusted by dropwise addition of ammonium hydroxide until a pH of 9.2 was reached. A voltage of +2.5 V was applied to a silver wire quasi-reference electrode for 20 minutes. After precipitation, the surface was rinsed in 1:1 water / methanol and the copolymer film was thermally cured at 150°C for 30 minutes. To remove the polymer coating, the HPHT BDD compact surface was polished using an aluminum oxide micropolish (0.05 μm, Buehler) with a cotton swab before rinsing with distilled water. Electrochemical characterization data were recorded following the above described procedure and after deposition of the insulating polymer film and after removal of the polymer coating by polishing.
[0079] For scanning electrochemical cell microscopy (SECCM) measurements, nanotubes (nanopipette) were drawn from borosilicate glass monotubes (1 mm outer diameter, 0.5 mm inner diameter, Harvard Apparatus) using a Sutter P-2000 laser puller (Sutter Instruments, USA). After drawing, the inner diameter of one end of the nanotube was within the range of 1 μm. The outer wall was silanized by immersing the nanotube in dichlorodimethylsilane (>99% purity, Acros) while argon was flowed to ensure that the inner sidewall was not silanized. This treatment minimizes the diffusion of the solution from the tube to the sample surface.
[0080] The nanotubes were filled with a solution containing 10 mM Ru(NH3)6Cl3 and 0.01 M KNO3, and a Ag / AgCl quasi-reference counter electrode (QRCE) was inserted behind the nanotubes. A series of voltammetric measurements were performed using the hopping mode (5 μm "hopping distance" or spatial resolution) and using the nanotubes at each pixel on a 200 × 200 μm area of the HPHT BDD compact (4.8 wt% AlB2 only) surface (working electrode). The potential applied to the QRCE was 10 V s -1The scan rate was swept from +1V to -1V, then back to +1V, and the current at the surface was recorded. All data analysis was performed using Matlab (R2014b, Mathworks). The crystal orientation of the compacted surface of the SECCM scan area was determined by electron backscatter diffraction (EBSD).
[0081] Field emission scanning electron microscopy (FE-SEM) was used to investigate the morphology and size of BDD particles produced after HPHT growth under two different boron doping conditions. Figure 3 FE-SEM images are shown. Figure 3 a and 3d show the powder morphology, Figure 3 b and 3e show the surface defects of individual particles, and Figure 2 c and 2f show the structure of the compact. Figure 3 a to 3c are HPHT BDD particles made with 3.6 wt% AlB2, and Figure 3 d to 3f are HPHT particles made with 4.8 wt% AlB2. Arrows indicate surface nucleation and circles indicate pores found on the particle surface.
[0082] The presence of crystallographic defects typical for highly doped BDDs was observed, including: surface nucleation (indicated by arrows, Figure 2 a, b and c), where small crystallites nucleate and grow on the faces of larger crystals, and on some crystal faces (particularly the major {111} face, indicated by green circles, Figure 2 b and e), and general deformation from perfect crystallization, especially at the corners of individual crystals ( Figure 2 b). Surface nucleation occurs as a result of an increasing number of defect sites on the growing BDD surface as added boron disturbs the diamond lattice. On the {111} face, each carbon atom is bonded to three carbon atoms, with one free bond through which the lattice extends. When a boron atom replaces a carbon atom located on a {111} face, there are no free bonds because it only has three valence electrons. As the crystal grows, the additional carbon atoms cannot be incorporated into the boron sites on the {111} face, leaving bald spots on the surface. Conversely, when boron replaces carbon on the {100} face, one boron atom is bonded to two carbon atoms and thus leaves one free bond to extend the lattice. This also reduces the number of defects along the <111> direction, which in turn explains why the {111} facets dominate at high boron concentrations, since in the crystal growth the fastest growing facets (in this case {100}) grow out leaving the slower facets dominant.
[0083] The surface of the particles is considered free of residual metallic impurities that were successfully removed during processing. It is important to note that Fe and Ni may still be present in small amounts as inclusions contained entirely within the BDD particles, but this does not affect the electrochemical properties since the electrochemical processes occur only at the interface between the surface and the solution.
[0084] FE-SEM images of the polished surface of the BDD compacts were also taken ( Figure 3 c and f). The presence of much smaller BDD particles known as fines was observed for the compacts produced during compaction and for the compacts that filled some of the small gaps where the BDD crystals were pushed together. Some small cracks and voids were also observed where the particles met, suggesting that this material may have porosity associated with it because there was no binder present to completely fill these gaps during compaction. Compared to 3.6 wt% AlB2 ( Figure 2 c) (where the BDD particles appear more separate and distinct), for the 4.8 wt% AlB2 additive sample ( Figure 2 f) A greater degree of connectivity between particles was observed, with fewer and smaller pores between particles.
[0085] like Figure 4 In Figure 2, Raman measurements were performed on two differently boron-doped compacts and compared with the spectra obtained for undoped diamond. Figure 4 a shows the Raman spectrum of undoped diamond, Figure 4 b shows the Raman spectrum of HPHT diamond prepared using 3.6 wt% AlB2 and Figure 4 c shows the Raman spectrum of HPHT diamond prepared using 4.8 wt% AlB2.
[0086] ~550cm -1 and ~1200cm -1 The presence of a peak at 550 cm (a signature of highly doped BDD and not observed in undoped samples) confirms the presence of boron in the diamond lattice. -1 The peak is believed to be attributed to the local vibration mode of the boron pairs in the lattice. The wide 1200 cm -1 The band corresponds to the maximum of the phonon density of states caused by the disorder introduced by boron doping. The diamond Raman line is relatively close to the intrinsic diamond line (1332.5 cm -1 ,like Figure 4 a) is also slightly red-shifted, such as Figure 4 b and 4c show that for 3.6 wt% AlB2 and 4.8 wt% AlB2, respectively, the peaks appear at 1330.83 cm -1 and 1329.15cm -1. The shift is due to scattering by boron impurities which cause tensile residual stress. A larger shift is observed for the 4.8 wt% AlB2 sample, indicating a higher level of boron doping than the 3.6 wt% AlB2 sample. A slight asymmetry of this peak is also observed due to the Fano resonance. The Fano effect arises due to quantum mechanical interference between discrete Raman phonon state transitions and interband transitions of energy continuous subbands, which is a result of the Fermi level shifting to the conduction band due to high levels of boron doping. There is no graphitic peak (G and D peaks are located at approximately 1560 cm -1 and 1360cm -1 ), indicating the lack of sp introduced during the growth or post-processing of the material 2 Carbon impurities. Raman spectra of the HPHT BDD pellets used to prepare the compacts were also acquired and the same key features were observed.
[0087] SIMS and GDMS analysis of boron-doped particles provide the boron dopant levels of both materials. 20 B atoms cm -3 When the amount of AlB2 added increases, showing an increase in boron concentration, only 4.8% of the material also shows an accompanying Fano resonance in Raman, which is a sign of metalloid doping. The nitrogen content was found to be two orders of magnitude lower than the boron content (Table 2), which is crucial because nitrogen atoms compensate for the boron atoms in the lattice, making them electrically inactive.
[0088] The boron concentration in the BDD does not vary linearly with the proportion of AlB2 in the reactants. A significant increase in the AlB2 addition results in only a small increase in the substitutional boron concentration results. This suggests that not all of the boron provided from the AlB2 boron source added to the reactants is incorporated into the growing diamond lattice.
[0089] Table 2 Boron concentration and nitrogen concentration obtained by GDMS and SIMS
[0090]
[0091] Electrochemical characterization was performed on the polished surfaces of two differently doped BDD compacts. Figure 5 HPHT BDD compacts with a) 3.6 wt% AlB2 and b) 4.8 wt% AlB2 are shown in 0.1 M KNO3 at 0.1 V s -1 Cyclic voltammograms recorded at a scan rate of . Figure 5 The solvent window obtained in a is wide, however the capacitive component C is significant. To calculate C, the voltage window is reduced to 0 V ± 0.1 V and Equation 1 is used:
[0092]
[0093] where i avis the average current at 0 V from the forward and backward sweeps, and ν is the scan rate (here 0.1 V s -1 ), A is the electrode geometric area. For polished CVD-grown BDD, it is usually reported 36 Capacitance is ~6-10μF cm -2 Here the C values are almost three orders of magnitude higher, with 3.14 mF cm obtained for 3.6 wt% AlB2 and 4.8 wt% AlB2, respectively. -2 and 2.64mF cm -2 Since the geometric area is used, the data strongly suggests that there is a large accessible surface area due to the porosity of the compacts, rather than a significant graphite contribution. In order to avoid electrochemical interference problems, no binder was added during compaction, so the remaining voids between the BDD particles remained unfilled. However, for some applications such as supercapacitors, high capacitance materials are desired. Porous electrodes also play a fundamental role in electrochemical fuel cell technology.
[0094] In order to provide information about the electrochemical properties of the material, Ru(NH3)6 3+ , which is due to its outer sphere properties and fast electron transfer kinetics. Under typical CV scan conditions for CVD-grown BDD, Ru(NH3)6 3+ The response appears very close to reversible (diffusion controlled), with less than 70 mV peak-to-peak separation ΔE p However, due to the very large background current, 1 mM Ru(NH3)6 cannot be fully discerned against the background. 3+ Oxidation and reduction peaks of redox electrochemistry ( Figure 5 a). Increase Ru(NH3)6 3+ Ten times the concentration ( Figure 5 d) improves this situation resulting in a ΔE of 0.04 for 3.6 wt% AlB2 and 4.8 wt% AlB2. p The values are 125mV and 104mV respectively. The larger ΔE p The values may be a sign of non-negligible material resistance, resulting in ohmic losses (iR) or less boron than expected in diamond. Since the Raman spectra obtained for 3.6 wt% and 4.8 wt% AlB2 compacts ( Figure 4 % AlB2 compacts, indicating high boron doping, so the effect of particle-to-particle contact resistance in the compacted material is likely the most significant factor. Although boron content may still play a role, as indicated by the lack of Fano resonance for the 3.6 wt% AlB2 compacts, it may also explain why lower capacitance and peak-to-peak separation are observed for the 4.8 wt% AlB2 compacts. However, the compact porosity also makes data analysis challenging, as the peak-to-peak separation is best quantitatively explained using planar non-porous electrodes.
[0095] In an attempt to remove the porosity contribution from the electrochemical response, a thin film of the insulating polymer polyphenylene ether was electrochemically coated onto all electrochemically accessible areas of the BDD surface. Then, only the top surface of the polymer was removed by gentle polishing with micronized alumina particles. Before coating with polyphenylene ether, 1 mM Ru(NH3)6 was expected. 3+ The CV (black line) is displayed on Figure 5 When the insulating coating was applied, no electrochemical response was observed due to blocking of all accessible electron transfer sites. After gentle polishing of the top surface, the CVs are now much more clearly defined, the currents are smaller, and the capacitive contribution is significantly reduced. This is probably due to the coating filling the subsurface pores and thus limiting the exposed BDD area to only the top surface of the compact. Determination of 1 mM Ru(NH3)6 3+ The peak-to-peak separation is 105 mV.
[0096] For higher resolution probing of compacted electrodes, SECCM was performed on polymer-free surfaces. Figure 7 a is an EBSD image of a SECCM scanned area on a 4.8 wt% AlB2 HPHT BDD compact. The white squares indicate the EBSD images recorded at Figure 7 b, Position of the cyclic voltammograms shown in 7c and 7d. Figure 6 b to 6d show the results of the experiments in 10 mM Ru(NH3)6Cl3 and 0.01 M KNO3 at 10 V s -1 Typical cyclic voltammograms recorded on facets 001, 101, and 111, respectively. Arrows indicate scan direction. All scans were performed in air.
[0097] EBSD proves that the surface consists of two types of regions, such as Figure 7 The two types of regions are well-defined crystalline particles with randomly distributed different plane orientations, and regions with unclear plane orientations. The latter reflects the regions of broken particles observed from FE-SEM images.
[0098] 10 mM Ru(NH3)6 was used on three separate grains 001, 101, 111 with ~1 μm diameter SECCM tip electrodes. 3+ The cyclic voltammograms recorded by redox electrochemistry show similar shapes independent of the surface structure ( Figure 6 ): The current remains constant at about 0 nA before gradually decreasing from about 0 V to -0.3 V (herein referred to as the starting potential) at the beginning of the scan, and then the current increases during the reverse scan, while the peak appears in a wide potential range of -0.2 V to +0.5 V. It was found that the changes in the peak position and the starting potential are independent of the crystallographic orientation.
[0099] The local capacitance value is estimated from Equation 1, where i av is the average current at 1 V from the forward and backward scans. The geometric electrode area A exposed during a single measurement is in the range of 2.5 ± 0.2 μm, measured from the meniscus remnant observed from the FE-SEM secondary electron image. The extracted capacitance value was found to be 17 ± 5 μF cm -2 , measured at the beginning of the SECCM scan. The distribution of the local capacitance as well as the starting potential values does not reveal any specific pattern indicating a uniform distribution across the surface around the average value.
[0100] The high current values observed by SECCM can be explained by the intrinsic submicron pores of the HPHT BDD material. Figure 7 The shapes of the cyclic voltammograms from b to 7d indicate that Ru(NH3)6 3+ Dynamic diffusion of the ions dominates, which makes the response insensitive to the crystallographic surface structure and indicates that the degree of boron doping is similar in each region. Because the scan area of each cyclic voltammogram is small, this indicates that not only does the HPHT BDD compact have pores due to cracks between particles, but the particle surface itself may be porous, which may be caused by the presence of crystallographic defects.
[0101] In order to remove the particle-particle contact resistance contribution from the electrochemical behavior, the electrochemical behavior of a single BDD particle was probed.
[0102] Figure 8 a schematically illustrates the structure of a device for probing the electrochemical behavior of a single BDD particle 1. A single BDD particle 2 is attached to a copper wire 5 via a Ti / Au contact 3 and an Ag epoxy resin 4 in an insulating housing 6. The BDD particle 2 is then encapsulated in an epoxy resin 7, which is polished to expose the surface of the single BDD particle 2.
[0103] Figure 8 b to 8d show HPHT BDD SPE in 0.1 M KNO3 at 0.1 V s -1 Cyclic voltammograms recorded at scan rates of 100 nm, showing b) the solvent window, c) a typical capacitance curve recorded, and d) HPHT BDD (4.8 wt% AlB2 additive) SPE in 1 mM Ru(NH3)6 3+ / 2+ and 0.1M KNO3 at 0.1, 0.05, 0.02 and 0.005V s -1 The electrode response in the CV was recorded at a scan rate of .
[0104] Studies were performed only on the 4.8 wt% AlB2 particles because Raman, GDMS and SIMS indicated that the boron level should be sufficient to achieve metal-like conductivity. Fig. 9 As shown in the above preparation and in Figure 8 FE-SEM image of the top surface of a silicon carbide polished HPHT BDD SPE shown in a. The white outline illustrates the exposed BDD.
[0105] The exposed electrode area is irregular in shape, with a geometric area of approximately 1.3×10 -4 cm 2 , measured using ImageJ. From the capacitance scan, 46 μF cm was determined using Equation 1 -2 This is probably an overestimate, as FE-SEM shows that the BDD surface is not featureless, so the geometric area underestimates the true electrochemically accessible area.
[0106] Figure 8 d is displayed in the scanning range of 0.005V s -1 To 0.1V s -1 1mM Ru(NH3)6 3+ / 2+ Figure 2. Cyclic voltammogram of the electrode. As the scan rate decreases, the shape of the cyclic voltammogram response changes from a peak to an almost S-shaped shape. This indicates that the electrode is at the size limit of microelectrode behavior for the mass transfer rate generated during the applied scan rate range. Linear diffusion dominates at higher scan rates, while radial contributions are significant at slower rates.
[0107] When the deviation from the theoretical 59 mV predicted by the Nernst equation for a single electron process at 25 °C is taken into account, Reversibility criterion (J. Collect. Czechoslov. Chem. Commun., 1937, 9, 12–21) was applied to the -1 The CV recorded at the scanning rate ( Figure 7 ), we get an E of 54mV 1 / 4 -E 3 / 4 values, indicating that the particles are sufficiently doped with substitutional boron to exhibit metallic conduction, although surface pores may suppress this value. Note that the cyclic voltammograms obtained do not fully represent the true microelectrode response due to the slightly oversized electrodes.
[0108] In summary, octahedral BDD particles were synthesized by metal-catalyzed HPHT technique in Fe-Ni-BC system at approximately 5.5 GPa and 1200 °C. High boron doping levels were achieved, estimated to be as high as 2.94 × 10 20 Atom cm -3 Increasing the amount of AlB2 additive in the growth mixture did result in slightly higher doping, the increase being disproportionate. It is clear from this observation and FE-SEM imaging, which identified many crystallographic defects, that doping with boron hinders diamond growth.
[0109] Although good electrochemical response was observed for single particles, the porosity of the HPHT BDD particles themselves and the compact resulted in an unusually high double layer capacitance. This unique property was confirmed by SECCM and polymer coating studies. However, the presence of this porosity does not reduce the potential of this material and can in fact be exploited for some applications, such as supercapacitor devices.
[0110] Although the present invention is particularly shown and described with reference to preferred embodiments, it will be appreciated by those skilled in the art that various changes in form and detail may be made without departing from the scope of the invention as defined by the appended claims. For example, although the above examples use AlB2 as a nitrogen getter and a boron source, it will be appreciated that a separate addition may be used to achieve the addition of boron and the removal of nitrogen from the reactants. For example, the boron source may be selected from amorphous boron, AlB2, MgB2 or other low melting point or low decomposition temperature borides, FeB, Mn4B or other transition metal borides. The nitrogen getter material source may be selected from Al, Ti, other elements of Group IVa in the periodic table (IUPAC), and other chemical species that form stable N compounds.
[0111] It should also be noted that while the boron doped synthetic HPHT diamond material described above is characterized in aqueous solution, it is envisaged that the material may be used in other types of solutions including organic solvents. As such, it will be appreciated that the characterization of the material is not intended to limit the use of the material in a range of applications.
Claims
1. An electrode comprising a synthetic high pressure and high temperature diamond material, wherein the synthetic high pressure and high temperature diamond material comprises: In 1×10 20 and 5×10 21 Atom / cm 3 The replacement boron concentration between ; No more than 10 19 Atom / cm 3 nitrogen concentration; and Where the electrodes have any of the following properties: In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution 3 / 4-1 / 4 ;and In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ A peak to peak separation ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution of p .
2. The electrode according to claim 1, wherein the sp 2 The carbon content is low enough that no non-diamond carbon peaks appear in the Raman spectrum of the electrode.
3. The electrode according to claim 1, wherein the synthetic high pressure and high temperature diamond material has a selected from at least 2×10 20 Boron atom cm -3 , at least 3×10 20 Boron atom cm -3 , at least 5×10 20 Boron atom cm -3 , and at least 7×10 20 Boron atom cm -3 The boron content of any item in.
4. The electrode of claim 1, comprising intergrown grains of synthetic high pressure high temperature diamond material.
5. The electrode of claim 1, comprising particles of synthetic high pressure high temperature diamond material dispersed in or on an electrically non-conductive matrix material.
6. The electrode according to claim 5, wherein the non-conductive matrix material is selected from any of polymers, insulating oils, and insulating inks.
7. The electrode of claim 1, comprising particles of synthetic high pressure high temperature diamond material dispersed in or on a conductive matrix material.
8. The electrode according to claim 7, wherein the conductive matrix material is selected from any of a conductive polymer, a non-diamond carbon support, and a conductive ink.
9. An electrode according to claim 1, comprising a container containing particles of synthetic high pressure high temperature diamond material, the container having at least one opening through which electrolyte can pass in use.
10. An electrode according to claim 9, wherein the container comprises at least one wall having pores through which the electrolyte can pass in use.
11. An electrode according to claim 1, comprising a compact of particles of synthetic high pressure high temperature diamond material.
12. An electrode according to claim 11, wherein the particles of synthetic diamond material have an average particle size selected from any of the ranges of 5 nm to 500 μm, 10 nm to 200 μm, 50 nm to 100 μm, and 100 nm to 10 μm.
13. A method for preparing an electrode comprising synthetic high pressure and high temperature diamond material, the method comprising: Provided is a synthetic high pressure high temperature diamond material having a 20 and 5×10 21 Atom / cm 3 The concentration of replacement boron between 19 Atom / cm 3 nitrogen concentration; and Forming synthetic high-pressure and high-temperature diamond material into electrodes.
14. The method of claim 13, wherein the step of forming the synthetic high pressure high temperature diamond material into an electrode comprises providing a reactant comprising the high pressure high temperature diamond material and a catalyst material; subjecting the reactants to a temperature greater than 1300°C and a pressure greater than 4.0 GPa to form a body comprising intergrown grains of diamond material; and The catalyst material is removed from the body to form an electrode.
15. The method of claim 13, wherein the step of forming the synthetic HPHT diamond material into an electrode comprises dispersing particles of HPHT diamond material in or on an electrically non-conductive matrix material.
16. The method of claim 13, wherein the step of forming the synthetic HPHT diamond material into an electrode comprises dispersing particles of the synthetic HPHT diamond material in or on a conductive matrix material.
17. The method of claim 13, wherein the step of forming the synthetic HPHT diamond material into an electrode comprises providing a container having at least one opening and placing particles of the synthetic HPHT diamond material in the container.
18. The method of claim 13, wherein the step of forming the synthetic HPHT diamond material into an electrode comprises compacting a plurality of particles of the synthetic HPHT diamond material at a pressure of at least 4.5 GPa and a temperature of at least 1400°C to form a compact.
19. Particles of synthetic high pressure and high temperature diamond material, comprising: In 1×10 20 and 5×10 21 Atom / cm 3 The substitutional boron concentration between ; and No more than 10 19 Atom / cm 3 nitrogen concentration; and Particles of synthetic high pressure, high temperature diamond material having any of the following characteristics: In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution 3 / 4-1 / 4 ;and In the presence of 0.1M KNO3 and 1mM Ru(NH3)6 3+ A peak to peak separation ΔE selected from any of less than 70 mV, less than 68 mV, less than 66 mV, and less than 64 mV measured with respect to a saturated calomel reference electrode in an aqueous solution of p .
20. The particle of synthetic high pressure high temperature diamond material according to claim 19, having a selected from at least 2×10 20 Boron atom cm -3 , at least 3×10 20 Boron atom cm -3 , at least 5×10 20 Boron atom cm -3 , and at least 7×10 20 Boron atom cm -3 The substitutional boron content of any item in.
Citation Information
Patent Citations
Boron-doped diamond
EP0518532A1
Novel diamond products and the manufacture thereof
US4042673A
Method of electrolysis employing a doped diamond anode to oxidize solutes in wastewater
US5399247A
Method of forming a boron-doped diamond film by chemical vapor deposition
US5635258A
Measuring concentrations of plural target substances by use of diamond electrode
US6106692A